Good Governance in Islam: The Nigerian Experience - Aminu, Muʻallimu Kamabari; Musaddad, Aliyu Ibrahim; Isah, Adamu Tanko (Universitas Islam Negeri Raden Intan Lampung, 2019)
This paper begins with an examination of the concept of good governance in Islam. The paper proceeds with a discussion on the precepts of good governance in Islam and the role of leadership in good governance. It is against this background that the paper looks at the Nigerian governance experience over the last few years. The paper concludes with some useful recommendations.